The Effect of Substituting Tapioca Flour with Taro Flour on Cooking Loss, pH and Organoleptic Value of Chicken Sausage - Ma'rifah, Siti; Imanuel, Robertho; Paulini; Pia, Laurentia Engelina (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
Chicken meat is one of the sources of animal protein that the Indonesian people widely favor. One of the processed chicken meats is sausage. Sausage is one of the processed meat products that the Indonesian people have come to recognized. Taro (Colocasia esculenta) is a type of tuber that is rich in carbohydrates, fiber, and has a fairly good nutritional content. Taro flour is widely used for food processing as a companion to wheat flour and tapioca flour. The purpose of the study was to determine the effect of substituting tapioca flour with taro flour on the physical quality (cooking loss), pH and organoleptic value (taste, color, aroma, and texture) of chicken sausage. The design used was a completely randomized design (CRD) with four treatments: P0 (0% of taro flour), P1 (10% of taro flour), P2 (15% of taro flour), and P3 (20% of taro flour), each with six replications. The results showed that the substitution of tapioca flour with taro flour had no significant effect (p > 0.05) on the physical quality or all organoleptic parameters. However, the higher proportion of taro flour used tended to decrease panelists liking of taste, color, aroma, and texture. Thus, taro flour can be used as an alternative to tapioca flour in making chicken sausage to a certain extent without significantly affecting the product’s quality, but based on panelist test results, 20% of taro flour represents 100% dislike.